TRANSPARANSI LAYANAN PENYAMPAIAN ASPIRASI MASYARAKAT PADA DEWAN PERWAKILAN RAKYAT DAERAH - Ineu Purwadewi Sundari (Socio Politica : Jurnal Ilmiah Jurusan Sosiologi, 2018)
This study examines the performance of the regional council in serving of channeling aspirations of the people in West Java, Indonesia. This is possible because West Java province is an autonomous regional authority to regulate and manage the interests of the community and Government Affairs at its own initiative based on the aspirations of the people. The study uses a qualitative approach in order to get the natural settings in which there were many behaviors and events occurred. This study also uses an institutional theory (institutionalism), because the theory could lead the researchers on the structure, regulation and institutional procedures which could have a significant impact on a public policy and it should not be ignored in policy analysis. This study finds that in order to carry out their functions as elected representatives, the members of the provincial representative council always make themselves available for the community. To that end, the members of the provincial parliament, among others, absorb and collect the aspirations of the constituents through regular working visits; accommodate and follow up the aspirations and complaints; and give morally and politically accountable to the constituencies. In addition to receiving complaints that come to the Parliament's office, public aspiration was performed on working visits on a regular basis by members of Regional Representative Council for each electoral district at the time of recess. In terms of transparency, all the services were conducted in a transparent manner. Even so, some people still doubt the veracity of such transparency.